Viability of diagnostic decision support for antenatal care in rural settings: findings from the Bliss4Midwives Intervention in Northern Ghana - Abejirinde, Ibukun-Oluwa Omolade (J Glob Health, 2019)
BACKGROUND: Antenatal screening is useful for early identification and management of high-risk pregnancies. In low-resource settings, provision of the full complement of tests is limited and diagnostic referrals incure additional costs for pregnant women. We assessed the viability of Bliss4Midwives (B4M) - a point-of-care diagnostic decision support device for decentralized screening of pre-eclampsia, gestational diabetes and anaemia during antenatal care (ANC). METHODS: The device was piloted in seven health facilities across two districts in Northern Ghana over a ten-month period. Health workers were expected to screen women at each ANC visit till delivery. All screening records from the device were automatically archived digitally and later downloaded. After removing duplicates or invalid entries, descriptive quantitative analysis was carried out with IBM SPSS Statistics (version 23). B4M usage behavior, diagnostic and referral outcome were analyzed. RESULTS: Health workers conducted 1323 partial or full antenatal screening on 940 women, resulting in decision support for 835 (88.8%) B4M beneficiaries. Diagnostic referral was eliminated for 708 (84.7%) beneficiaries, with 335 (40.1%) of these from facilities without on-site diagnostic alternatives. Of visits with complete data, 92/559 (16.4%) women were screened in their first trimester, 28/940 (2.9%) had 4+ B4M visits and 107/835 (12.8%) women were recommended for urgent referral to a higher-level facility on the first visit. Follow-up screenings flagged an additional 17 women for urgent referral with 10 cases of repeated alerts in five women. Wide variations between high (9 months use) and low adopting (1.5 months use) facilities were observed, with some similarities in usage trend. CONCLUSIONS: B4M helped decentralize ANC screening and decrease unnecessary referrals. Project outcomes were influenced by implementation strategy, technical features and behavioural dispositions of users and beneficiaries.